IDENTIFICATION, DIGITAL DOCUMENTATION AND CONSERVATION OF HISTORIC MONUMENTS IN PAKISTAN: A CASE OF SHEESH MEHAL LAHORE - Asia Jabeen; Dr. Shama Anbrine; Prof. Dr. Yusuf Awan; Prof. Dr. Neelum Naz (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper emphasizes the significance of preserving historic monuments, emphasizing their role as tangible records of human history. It highlights the necessity of conserving such heritage assets for the sustainable development of historic cities, with a particular focus on the documentation process. The case study revolves around Sheesh Mehal in Lahore, chosen for its historical importance and the application of digital tools like Total Station and Terrestrial Laser Scanner (TLS) in its preservation efforts. By evaluating the strengths and weaknesses of both documentation techniques, the paper aims to deepen our understanding of the intricate spatial dynamics within heritage sites. Sheesh Mehal, situated within the Shah Burj of Lahore Fort and commissioned by Mughal Emperor Shah Jahan in 1631-32 A.D., holds a prominent position among the 21 significant monuments constructed by the Mughal rulers within Lahore Fort. Its recognition by the Indian Department of Archaeology in 1927, subsequent protection under the Antiquities Act by the Federal Department of Archaeology, Pakistan in 1975, and designation as a UNESCO World Heritage Site in 1981 underline its cultural and historical importance. The digital documentation of Sheesh Mehal, conducted by the Agha Khan Cultural Services of Pakistan (AKCSP) in 2017 using Total Station and by the Walled City Lahore Authority (WCLA) in 2022 using Terrestrial Laser Scanning, exemplifies the application of modern technologies in heritage preservation. In conclusion, the paper provides an analysis of the precision and accuracy of digital documentation techniques, shedding light on their efficacy in capturing and preserving the intricate details of historic monuments. This assessment contributes to the ongoing discourse on leveraging digital tools for the documentation and conservation of heritage sites, ensuring their legacy for future generations.